Purple Urine Bag Syndrome in a Paraplegic Woman with a Long-Term Indwelling Catheter and Asymptomatic Urinary Tract Infection: A Case Report - Kothsompong, Hathaimas (ASEAN Journal of Rehabilitation Medicine, 2021)
Objectives: To report on points of concern in a paraplegic patient with a neurogenic bladder who presented with purple urine in a urine bag. Study design: A case report. Setting: Department of Rehabilitation Medicine, Maharat Nakhon Ratchasima Hospital, Thailand. Subjects: A 32-year-old paraplegic woman with long-term use of an indwelling catheter. Methods: The patient’s medical record, including demographic data, clinical presentation and laboratory results as well as urologic ultrasonography, treatment, and outcome were reviewed. Results: A patient with an indwelling transurethral catheter presented with a second episode of smelly purple urine for three days. She had no fever. She remained in bed due to an undiagnosed right hip fracture, a pressure ulcer, and chronic osteomye-litis of the right greater trochanter. A urine strip showed positive nitrite and a culture showed the presence of E. coli. Ultrasono-graphy showed no renal or bladder stones. After three days of intravenous antibiotic treatment, the purple urine completely resolved. Conclusions: Paraplegic patients with a long-term indwelling catheter, asymptomatic urinary tract infection with purple urine should receive prompt and appropriate antibiotic therapy. Keywords: purple urine, urinary tract infection, urinary catheter, indwelling catheter, paraplegia